THE EFFECT OF DRONE USE AND DIGITALISATION TRAINING ON WORK PERFORMANCE MEDIATED BY WORK MOTIVATION AT PTPN IV REGIONAL I - Mulia Surya Darma; Siti Mardiana; Dian Noviandri (JURNAL AGRIMANSION, 2026)
PT Perkebunan Nusantara (PTPN) is currently undergoing a significant digital transformation phase by integrating drone technology into its plantation operations. PTPN already has Unmanned Aerial Vehicles (UAVs)/drones, which are mainly used for mapping areas and counting oil palm trees. The total plantation area of 101,733.53 hectares is supported by 36 drone units, with technology acceptance influenced by perceived usefulness and perceived ease of use. At PTPN IV, the proportional distribution of drones supports the perception that this technology is useful (speeding up monitoring) and easy to use (through training), thereby encouraging widespread adoption and increased productivity. The researchers aimed to analyse the effect of drone use and digitalisation training on work performance through work motivation. This study used a quantitative approach combined with descriptive qualitative data to reinforce the findings through interviews with structural equation modelling data analysis with a sample size of 83 employees. The results of the study indicate that digital transformation through the use of drones and digitalisation training plays an important role in increasing employee motivation and work performance at PTPN IV, although the effect is not entirely direct. The use of drones has been shown to be more dominant in driving work motivation than directly improving work performance, indicating that new technology tends to increase enthusiasm, interest, and perceptions of work progress before actually impacting performance output. Conversely, digitalisation training provides a more consistent and stronger contribution to work performance, both directly and through increased work motivation. Work motivation itself acts as an intervening variable that strengthens the relationship between technology and performance, although its direct influence on work performance is not yet fully optimal.